Health of the black immigrant population during the COVID-19 pandemic: a scoping review (Research, Society and Development, 2022)
The black population has had a distinct impact on incidence and lethality during the COVID-19 pandemic. On immigrants, there are gaps in their health reality, few countries identify the nationality of the infected population or those who died because of COVID-19 in the notification forms. The aim of this research is to identify the health situation of black immigrants in the world during the COVID-19 pandemic. The method chosen was a scoping review, with the formulation of a research question that sought information about the health situation of black immigrants during the COVID-19 pandemic. Primarily 807 documents were founded, among them, there were petitions, books, manuals, reports, editorials, letters to the editor, and articles. After applying the inclusion and exclusion criteria, as well as removing repeated files, 13 materials remained to compose the final sample of this review, including articles, letters to the editor, editorial, and commentary. The data point to silence from the academic community and a lack of in-depth debates on how structural racism is decisive in the health of the black population, as well as material that discussed the health of the immigrant population in general.